Incorporation of Low Concentrations of Gold Nanoparticles: Complex Effects on Radiation Response and Fate of Cancer Cells - Dobešová, Lucie; Gier, Theresa; Kopečná, Olga; Pagáčová, Eva; Vičar, Tomáš; Bestvater, Felix; Toufar, Jiří; Bačíková, Alena; Kopel, Pavel; Fedr, Radek; Hildenbrand, Georg; Falková, Iva; et al. (Pharmaceutics, 2022)
(1) Background: In oncology research, a long-standing discussion exists about pros and cons of metal nanoparticle-enhanced radiotherapy and real mechanisms behind the tumor cell response to irradiation (IR) in presence of gold nanoparticles (GNPs). A better understanding of this response is, however, necessary to develop more efficient and safety nanoparticle (NP) types designed to disturb specific processes in tumor cells. (2) Aims and Methods: We combined 3D confocal microscopy and super-resolution single molecule localization microscopy (SMLM) to analyze, at the multiscale, the early and late effects of 10 nm-GNPs on DNA double strand break (DSB) induction and repair in tumor cells exposed to different doses of photonic low-LET (linear energy transfer) radiation. The results were correlated to different aspects of short and long-term cell viability. SkBr3 breast cancer cells (selected for the highest incidence of this cancer type among all cancers in women, and because most breast tumors are treated with IR) were incubated with low concentrations of GNPs and irradiated with 60Co γ-rays or 6 MV X-rays. In numerous post-irradiation (PI) times, ranging from 0.5 to 24 h PI, the cells were spatially (3D) fixed and labeled with specific antibodies against γH2AX, 53BP1 and H3K9me3. The extent of DSB induction, multi-parametric micro- and nano-morphology of γH2AX and 53BP1 repair foci, DSB repair kinetics, persistence of unrepaired DSBs, nanoscale clustering of γH2AX and nanoscale (hetero)chromatin re-organization were measured by means of the mentioned microscopy techniques in dependence of radiation dose and GNP concentration. (3) Results: The number of γH2AX/53BP1 signals increased after IR and an additional increase was observed in GNP-treated (GNP(+)) cells compared to untreated controls. However, this phenomenon reflected slight expansion of the G2-phase cell subpopulation in irradiated GNP(+) specimens instead of enhanced DNA damage induction by GNPs. This statement is further supported by some micro- and nano-morphological parameters of γH2AX/53BP1 foci, which slightly differed for cells irradiated in absence or presence of GNPs. At the nanoscale, Ripley's distance frequency analysis of SMLM signal coordinate matrices also revealed relaxation of heterochromatin (H3K9me3) clusters upon IR. These changes were more prominent in presence of GNPs. The slight expansion of radiosensitive G2 cells correlated with mostly insignificant but systematic decrease in post-irradiation survival of GNP(+) cells. Interestingly, low GNP concentrations accelerated DSB repair kinetics; however, the numbers of persistent γH2AX/53BP1 repair foci were slightly increased in GNP(+) cells. (4) Conclusions: Low concentrations of 10-nm GNPs enhanced the G2/M cell cycle arrest and the proportion of radiosensitive G2 cells, but not the extent of DNA damage induction. GNPs also accelerated DSB repair kinetics and slightly increased presence of unrepaired γH2AX/53BP1 foci at 24 h PI. GNP-mediated cell effects correlated with slight radiosensitization of GNP(+) specimens, significant only for the highest radiation dose tested (4 Gy).
Keywords: DNA repair nano-clusters; DNA double strand breaks (DSBs); nanoparticle-enhanced cancer radiotherapy; DNA repair; single-molecule localization microscopy (SMLM); ionizing radiation-induced (repair) foci (IRIF); gold nanoparticles (GNP); chromatin nano-architecture rearrangements